Bahasa Inggris - Efie Indrianti; Juan Prianto; Martiningsih; Rizal Fahruroji; Rini Marlina; Ineu Widiana (Sekolah Tinggi Teknologi Wastukancana, 2025)
Polyester is a type of polymer commonly used in the production of bottle packaging and textile products. However, polyester takes hundreds of years to decompose naturally, making polyester waste management a critical issue. One of the emerging solutions is the production of recycled polyester. In Indonesia, the utilization of recycled polyester has seen significant growth, particularly in the textile and fashion industries. Several studies have shown that recycled polyester exhibits the same tensile strength and tear resistance as virgin polyester, but with higher stiffness, making it more suitable for geotextile applications. For example, polyester-based plastics are often used as protection in road casting. This study aims to develop nonwoven geotextile using a blend of recycled polyester and low melt polyester fibers with a basis weight of 150 g/m2. Test results indicate that the geotextile fabric has a tensile strength of 240 N, a tear strength of 109.06 N, and a concrete compressive strength of 18.91 MPa.